2008
DOI: 10.1016/j.radphyschem.2008.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of solvated electrons with imidazolium cations in ionic liquids

Abstract: We examined formation of solvated electrons in several ionic liquids composed of ammonium, pyrrolidinium and piperidinium cations by observing absorption spectra in the visible and near-infrared regions using pulse radiolysi. We also examined reactions of the solvated electrons with imidazolium cations in the ionic liquids. The reaction rate constants were an order of magnitude faster than the diffusion limited rate calculated from the viscosity. The electrons before full solvation (dry electrons) reacted effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 18 publications
5
43
0
Order By: Relevance
“…The reaction constants of three C2-alkyl imidazolium cations [1-ethyl-2,3-dimethylimdazolium, 1-butyl-2,3-dimethylimdazolium (BMMI + ), 1-hexyl-2,3-dimethylimdazolium] with hydrated electrons were examined, and were found to be very close each other, 5.9×10 9 , 5.5×10 9 , and 5.1×10 9 L mol −1 s −1 , respectively, whereas that of the BMI + cation was 1.8×10 10 L mol −1 s −1 . These findings are quite similar to those of Takahashi et al [19]. They found that alkylation of the imidazolium suppresses reactivity with dry electrons.…”
Section: Reactions With Hydrated Electronssupporting
confidence: 92%
“…The reaction constants of three C2-alkyl imidazolium cations [1-ethyl-2,3-dimethylimdazolium, 1-butyl-2,3-dimethylimdazolium (BMMI + ), 1-hexyl-2,3-dimethylimdazolium] with hydrated electrons were examined, and were found to be very close each other, 5.9×10 9 , 5.5×10 9 , and 5.1×10 9 L mol −1 s −1 , respectively, whereas that of the BMI + cation was 1.8×10 10 L mol −1 s −1 . These findings are quite similar to those of Takahashi et al [19]. They found that alkylation of the imidazolium suppresses reactivity with dry electrons.…”
Section: Reactions With Hydrated Electronssupporting
confidence: 92%
“…Several pulse radiolysis studies on ionic liquids (Behar et al, 2001;Behar et al, 2002;Grodkowski and Neta, 2002a-c;Wishart and Neta, 2003;Grodkowski et al, 2003;Wishart et al, 2005;Kato, et al, 2007;Takahashi et al, 2007;Kimura et al, 2007) have been reported. The researches indicate that, for the imidazolium ionic liquids, dry electrons produced by ionization before full solvation are rapidly scavenged by the solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical reactivity in ionic liquids has been begun to be studied. Several nanosecond pulse radiolysis studies of ionic liquids (Behar et al, 2001(Behar et al, , 2002Grodkowski and Neta, 2002a-c;Wishart and Neta, 2003;Grodkowski et al, 2003;Katoh et al, 2007;Asano et al, 2007;Takahashi et al, 2007;Kimura et al, 2007) and picosecond studies (Wishart et al, 2005) have been published. The researches indicate that, for the imidazolium ionic liquids, the electrons produced by ionization are rapidly scavenged by the solvent molecules before they become fully solvated, while the electrons in the ammonium ionic liquids are solvated quickly to form the solvated electrons.…”
Section: Picosecond Dynamics Of Solvated Electrons In Ionic Liquidmentioning
confidence: 99%